Association of oxidative balance score with all-cause mortality among individuals with chronic kidney disease: a cohort study - Ying Lan; Haoxian Tang; Zhimei Lin; Chao Huang; Lvlin Chen (BMC, 2024)
Abstract Background The Oxidative Balance Score (OBS) is employed for evaluating the body's overall level of oxidative stress. This study aimed to investigate the association between OBS and mortality in individuals with chronic kidney disease (CKD) using a cohort study design. Methods We used data from adult participants(≥ 20 years old) in the National Health and Nutrition Examination Survey (NHANES) from 1999 to 2018. CKD is diagnosed based on the Kidney Disease Improving Global Outcomes (KDIGO) guidelines. OBS, which consists of 16 dietary factors and 4 lifestyle factors, categorized into pro-oxidants and antioxidants, with a total score range of 0 to 40 .The OBS was divided into four quartiles (Q1 to Q4), with Q1 (5-12), Q2 (13-18), Q3 (19-24), and Q4 (25-36). We excluded patients with missing data on OBS, CKD, and key covariates.Cox regression analysis were used to examine the relationship between OBS and all-cause mortality in CKD patients. Sensitivity analyses included subgroup analysis and multiple imputation. Results We included a total of 3,984 patients with CKD. During an average follow-up period of 103 months, 1,263 cases (31.7%) of all-cause mortality were recorded. In the fully adjusted model, compared to Q1 the hazard ratios (HRs) and 95% confidence intervals (CIs) for Q4 were as follows: OBS 0.80 (0.68, 0.95) (p = 0.012), dietary OBS 0.78 (0.66, 0.92) (p = 0.003), and lifestyle OBS 0.83 (0.70, 0.99) (p = 0.038). Our sensitivity analyses further confirmed the robustness of these results. Conclusions Higher OBS was negatively correlated with all-cause mortality risk in American adults with CKD.